2015
DOI: 10.1556/achrom.27.2015.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Matrix Solid-Phase Dispersion and Liquid—Solid Extraction Methods Followed by Solid-Phase Extraction in the Analysis of Selected Furanocoumarins fromPimpinellaRoots by HPLC—DAD

Abstract: Summary. The use of matrix solid-phase dispersion (MSPD) was tested to extract some coumarins (umbelliferone, xanthotoxin, isopimpinellin, bergapten, and pimpinellin) from Pimpinella roots. The method was compared with liquid-solid extraction methods (LSE) such as accelerated solvent extraction (ASE), ultrasound-assisted extraction (USAE) and Soxhlet extraction followed by solid-phase extraction (SPE). Several methanol concentrations and temperature conditions were examined during the liquidsolid extraction te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Additionally, the phytochemical profile of P. anthriscoides was characterized and aegelinol ( 267 ), psoralen ( 268 ), imperatorin ( 269 ), is oimperator in ( 270 ), 3-(1,1-dimethylallyl)herniarin ( 271 ), peucedanin ( 272 ), and xanthyletin ( 273 ) were identified [ 65 ]. Some investigations [ 70 , 71 , 72 , 73 ] found that abundant linear coumarins ( 274 – 280 ) existed in the root and seed extract of P. anisum , among which isopimpinellin ( 274 ) and methoxsalen ( 275 ) were associated with the inhibitory activity of the cytochrome P450 1A2 isozyme in healthy adults. In addition, umbelliprenin ( 276 ) was proven to be an original skin-whitening agent ( Figure 6 , Table 5 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Additionally, the phytochemical profile of P. anthriscoides was characterized and aegelinol ( 267 ), psoralen ( 268 ), imperatorin ( 269 ), is oimperator in ( 270 ), 3-(1,1-dimethylallyl)herniarin ( 271 ), peucedanin ( 272 ), and xanthyletin ( 273 ) were identified [ 65 ]. Some investigations [ 70 , 71 , 72 , 73 ] found that abundant linear coumarins ( 274 – 280 ) existed in the root and seed extract of P. anisum , among which isopimpinellin ( 274 ) and methoxsalen ( 275 ) were associated with the inhibitory activity of the cytochrome P450 1A2 isozyme in healthy adults. In addition, umbelliprenin ( 276 ) was proven to be an original skin-whitening agent ( Figure 6 , Table 5 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…XAT, as a component of furanocoumarins, is widely distributed in the roots of Angelica sinensis, celery and lentils (Najda et al, 2015). Currently, the main methods for extracting coumarins include MSPD (Oniszczuk et al, 2015), supercritical fluid chromatography (SFC) and pressurized liquid extraction (PLE) (Pokrovskii et al, 2014; Skalicka‐Wozniak & Glowniak, 2012). However, coumarin components in plants often coexist in a variety of mixtures with similar structures and polarities, which are difficult to be separated by conventional solvent and crystallization methods, and are generally separated and purified by chromatographic separation methods, including HPLC‐DAD (Farooq et al, 2014; Ma et al, 2022), LC–MS (Hahnel, Dormann, Nitsopoulos, Friedle, & Ahrens, 2017), and UHPLC‐Q‐TOF‐MS (Tian et al, 2017).…”
Section: Chemistry Of Xatmentioning
confidence: 99%